Психологічні особливості феномену свідомості бідності - Плеханов, Д. В. (ХНУРЕ, 2021)
The problem of poverty in Ukraine currently affects a large part of the population. One of the factors that contribute poverty as the quality of life of the people is such a poverty consciousness. The article analyze the signs of poverty consciousness (fearing to the future, pessimistic expectations, suspicion and doubts about others etc.). It is pointed out that the thinking of a person with the poverty consciousness is recognized by the predisposition to think with the help of stereotypes. Some recommendations are фprovided for overcoming the negative manifestations of poverty consciousness.
Keywords: філософія